Association between the depressive symptom trajectories and all-cause mortality in Chinese middle-aged and elderly adults - Yayun Fan; Dingliu He; Lin Chen; Chunxia Ge (Scientific Reports)
Abstract Previous studies reported that depressive symptoms were associated with a high risk of all-cause mortality. However, the effect of different long-term depressive symptom trajectory patterns on the risk of all-cause mortality has not been evaluated. Our research aimed to explore the association between different depressive symptom trajectories and the risk of all-cause mortality in Chinese adults. The data we used were from the China Health and Retirement Longitudinal Study. In total, 13,624 subjects aged over 45 years were ultimately included in the analysis. Group-based trajectory modeling was used to identify the different trajectories of depressive symptoms. The multivariable Cox regression model was used to examine the association between long-term depressive symptom trajectories and all-cause mortality. The results show that a total of five depressive symptom trajectories were identified in our study, including stable-low, stable-moderate, increasing, decreasing and stable-high. Compared with individuals in the stable-low depressive symptom trajectories group, those in the increasing and stable-high trajectory groups possessed a greater mortality rate, with a multivariable-adjusted hazard ratio (95% CIs) for mortality were 1.30 (1.06, 1.60) and 1.59 (1.26, 2.02), respectively. In addition, we have not identified the significant risk of all-cause mortality in people with decreased and stable-moderate symptom trajectories. Moreover, the risk of all-cause mortality had an increasing trend among the different trajectory groups. In the sensitivity analysis, the association was robust in most of the subgroups. In conclusion, people with increasing and persistent higher depressive symptom trajectories were associated with an increased risk of all-cause mortality.